2002
DOI: 10.1073/pnas.142005099
|View full text |Cite
|
Sign up to set email alerts
|

Sialyltransferase ST3Gal-IV operates as a dominant modifier of hemostasis by concealing asialoglycoprotein receptor ligands

Abstract: A number of poorly characterized genetic modifiers contribute to the extensive variability of von Willebrand disease, the most prevalent bleeding disorder in humans. We find that a genetic lesion inactivating the murine ST3Gal-IV sialyltransferase causes a bleeding disorder associated with an autosomal dominant reduction in plasma von Willebrand factor (VWF) and an autosomal recessive thrombocytopenia. Although both ST3Gal-IV and ST6Gal-I sialyltransferases mask galactose linkages implicated as asialoglycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
185
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(191 citation statements)
references
References 45 publications
6
185
0
Order By: Relevance
“…treatment with either AUS NA (5 U/kg) or PBS. Plasma was isolated for measurements of the abundance or activity of specific blood coagulation factors, as previously described (24,25). Measurements of glycoprotein abundance were obtained with anti-factor antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…treatment with either AUS NA (5 U/kg) or PBS. Plasma was isolated for measurements of the abundance or activity of specific blood coagulation factors, as previously described (24,25). Measurements of glycoprotein abundance were obtained with anti-factor antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…treatment with either AUS NA (5 U/kg) or PBS. Ratios of exposed galactose per unit of protein antigen were calculated as indicated and as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
“…One of the very few parameters that has been reported to date to influence VWF clearance is the VWF glycosylation profile (12,(21)(22)(23)(24). For instance, by using an animal model it has been shown that, in the absence of the enzyme ST3Gal-IV, the half-life of endogenous VWF is reduced 2-fold (24).…”
mentioning
confidence: 99%
“…For instance, by using an animal model it has been shown that, in the absence of the enzyme ST3Gal-IV, the half-life of endogenous VWF is reduced 2-fold (24). Moreover, in a patient group referred to the hospital for real or suspected bleeding disorder, reduced ST3Gal-IV-mediated sialylation was observed to be associated with reduced VWF plasma levels (24).…”
mentioning
confidence: 99%
“…The addition of Sia is catalyzed by a family of 20 sialyltransferase enzymes, which transfer Sia via 2-3, 2-6 and 2-8 linkages to various glycan acceptors [46]. The disruption of sialyltransferase genes in mice often results in immune and hematologic phenotypes [47][48][49]. Very recently, mutations in the 2-3 sialyltransferase gene ST3GAL3 (OMIM ID: 606494) have been associated with nonsyndromic mental retardation [50].…”
Section: 2-3 Sia-transferase IIImentioning
confidence: 99%